Pengaruh E-Learning Sebagai Pengembangan Karir Terhadap Karyawan Generasi Milenial Di Bank Central Asia (BCA) - Dasep Supriatna; Felisia Purnawanti; Deddy Novie Citra Arta; Rinovian Rais; Anggara Setya Saputra (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
The potential of human resources owned, companies in Indonesia have challenges in managing human resources, especially the millennial generation. The increasing growth and development of companies in Indonesia has a positive impact on society by expanding employment opportunities so that it will reduce the unemployment rate. One of the efforts to retain employees is that companies must pay attention to career development for each of their employees, especially for millennial generation employees who have good performance. There are several problems in the career development process in the company that is the object of research, millennial generation employees who cannot develop their careers in the company where they work, even though employees feel they have done a good job. The research methods in this study were e-learning and interview methods as well as giving questionnaires to research subjects. The research subjects in this study were millennial generation employees at Bank Central Asia (BCA). Learning is both a strategy and a solution for an organization/company as well as individuals to adapt and take effective action to create a competitive advantage. Companies need to improve the performance of their employees in order to excel and be successful in achieving the organization's strategic goals. PT Bank BCA realizes that development and training are efforts to create quality human resources. Thus, e-learning is one of the learning methods used in development and training for the millennial generation.